The employee readiness towards Radio Frequency Identification (RFID) Technology in sure-reach Worldwide Express Sdn. Bhd. / Nurul Adzwa Abu Bakar - Abu Bakar, Nurul Adzwa (Faculty of Business and Management, 2009)
RFID has been identified as one of the ten greatest contributory technologies of the twenty-first century. Companies lined up to use RFID and employer experts to improve the efficiency of their operations to gain competitive advantages over time. This paper will study on the employee readiness towards radio frequency identification (RFID) technology in Sure-Reach Worldwide Express Sdn. Bhd. The respondent that involves in the survey and evaluating are employees in headquarters at Petaling Jaya only. The data are collected from questionnaires. The analysis that been used in this research are descriptive analysis and independent samples T-test. It is clear that knowledge and experience are equally important in order to determine the employee readiness. Base on the results of the findings, the researcher has concluded that the employees at Sure- Reach Worldwide Express Sdn. Bhd. are ready to adopt technology change.